Utilização de resíduos da indústria calçadista em blendas de polietileno e polipropileno reciclados provenientes de equipamentos eletroeletrônicos (REEE) - Barrios, Christian Camilo Cuello (2019)
A few years ago, a considerable increase occurred in the production, the consumption, and the generation rate of solid plastic waste (RSP). Waste electrical and electronic equipment (WEEE) falls into the category of high value and hazardousness, which is not appropriate to be disposed in landfills due to economic and environmental unfeasibility. On the other hand, fabrics and rubbers generated by the footwear industry are sent to landfills due to the difficulty of reintroduction in the production processes. In this context, the goal of the present work was the development of polymeric composites with the incorporation of different contents (10 and 20 wt%) of tennis residue (TW) in the recycled Polyethylene (PE) and Polypropylene (PP) blend from WEEE, compatibilized with Maleic Anhydride (MA). The materials were molded by extrusion-injection, and the composition with the best mechanical properties was also molded by hot compression, aiming to compare both molding methods and choose the more suitable productive method. For this, the developed mixtures were characterized by mechanical tests (flexural, tensile, impact and hardness), thermogravimetric analysis (TGA / DTG), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). The mixture with the best mechanical properties used 10% TW, 6% MA and PP/PE in equal proportion, improving both the flexural and the tensile strengths compared to the properties of untreated PE and PP polymers. An improvement in the impact resistance was observed due to the addition of TW and MA. Through thermal analysis, it was observed that the incorporation of TW in the PE/PP blend practically did not change the melting temperature. In this sense, the incorporation of TW into the PE/PP blend has shown satisfactory results, enabling the recycling of these three different wastes, while promoting the possibility of their reinsertion the productive process and providing information to allow the development of new products in the direction of the circular economy.